A Self‐Assembled Bicontinuous Cubic Phase with a Single‐Diamond Network. (23rd April 2019) - Zeng, Xiangbing; Poppe, Silvio; Lehmann, Anne; Prehm, Marko; Chen, Changlong; Liu, Feng; Lu, Huanjun; Ungar, Goran; Tschierske, Carsten
Abstract: The first single‐diamond cubic phase in a liquid crystal is reported. This skeletal structure with the F d 3 ‾ m space group is formed by self‐assembly of bolaamphiphiles with swallow‐tailed lateral chains. It consists of bundles of π‐conjugated p‐terphenyl rods fused into an infinite network by hydrogen‐bonded spheres at tetrahedral four‐way junctions. We also present a quantitative model relating molecular architecture to the space‐filling requirements of six possible bicontinuous cubic phases, that is, the single‐ and double‐network versions of gyroid, diamond, and "plumber′s nightmare". Abstract : Flüssigkristalliner Diamant : Das erste Flüssigkristallsystem mit Diamantstruktur entsteht durch spontane Selbstorganisation von bolaamphiphilen Molekülen. In dieser kubischen flüssigkristallinen Phase mit der Raumgruppe F d 3 ‾ m ersetzen die gebündelten Stäbchen die C‐C‐Bindungen und die polaren sphärischen Mizellen die C‐Atome des Diamantgitters.